Sword-Like Trauma to the Shoulder with Open Head-Splitting Fracture of the Head - Andreas Panagopoulos; Konstantinos Pantazis; Ilias Iliopoulos; Ioannis Seferlis; Zinon Kokkalis (Case Reports in Orthopedics)
Head-splitting fractures occur as a result of violent compression of the head against the glenoid; the head splits and the tuberosities may remain attached to the fragments or split and separate. Isolated humeral head-splitting fractures are rare injuries. Favorable results with osteosynthesis can be difficult to achieve because of the very proximal location of the head fracture and associated poor vascularity. We present a case of a 67-year-old man who sustained a severe, sword-like trauma to his left shoulder after a road traffic accident with associated isolated open Gustilo-Anderson IIIA humeral head-splitting fracture. Bony union was achieved with minimal internal fixation but the clinical outcome deteriorated due to accompanying axillary nerve apraxia. To our knowledge, this type of sword-like injury with associated humeral head-split fracture has not previously been reported.